Clarithromycin and endoscopic sinus surgery for adults with chronic rhinosinusitis with and without nasal polyps: study protocol for the MACRO randomised controlled trial - Philpott, C; Le Conte, S; Beard, D; Cook, J; Sones, W; Morris, S; Clarke, C; Thomas, M; Little, P; Vennik, J; Lund, V; Blackshaw, H; et al. (BioMed Central, 2019)
Background Chronic rhinosinusitis (CRS) is a common source of ill health; 11% of UK adults reported CRS symptoms in a worldwide population study. Guidelines are conflicting regarding whether antibiotics should be included in primary medical management, reflecting the lack of evidence in systematic reviews. Insufficient evidence to inform the role of surgery contributes to a fivefold variation in UK intervention rates. The objective of this trial is to establish the comparative effectiveness of endoscopic sinus surgery (ESS) or a prolonged course of antibiotics (clarithromycin) in adult patients with CRS in terms of symptomatic improvement and costs to the National Health Service compared with standard medical care (intranasal medication) at 6 months. Methods/design A three-arm parallel-group trial will be conducted with patients who remain symptomatic after receiving appropriate medical therapy (either in primary or secondary care). They will be randomised to receive: (1) intranasal medication plus ESS, (2) intranasal medication plus clarithromycin (250 mg) or (3) intranasal medication plus a placebo. Intranasal medication (current standard medical care) is defined as a spray or drops of intranasal corticosteroids and saline irrigations. The primary outcome measure is the SNOT-22 questionnaire, which assesses disease-specific health-related quality of life. The study sample size is 600. Principal analyses will be according to the randomised groups irrespective of compliance. The trial will be conducted in at least 16 secondary or tertiary care centres with an internal pilot at six sites for 6 months. Discussion The potential cardiovascular side effects of macrolide antibiotics have been recently highlighted. The effectiveness of antibiotics will be established through this trial, which may help to reduce unnecessary usage and potential morbidity. If ESS is shown to be clinically effective and cost-effective, the trial may encourage earlier intervention. In contrast, if it is shown to be ineffective, then there should be a significant reduction in surgery rates. The trial results will feed into the other components of the MACRO research programme to establish best practice for the management of adults with CRS and design the ideal patient pathway across primary and secondary care.